A Critical and Maternal Narrative Approach to Practice, Enhancing Recognition and Solidarity with Ambivalent Representations. Issue 5 (20th October 2017) - McGinty, Carol
Abstract : This is a conceptual paper that uses a critical practice approach to how a social worker's interpretive lens may transform after they become a parent. With a composite case example, I reflect on my own biographical maternal narrative, which aims to enhance the recognition and solidarity with ambivalent representations in the journey of motherhood. I conceptualise maternal narratives with Fook's critical approaches to practice framework (2016). I interweave a composite case example that I had direct experience and privilege of working with, along with my own biographical experience of mothering. The central themes that have emerged from my critical reflective analysis are; ambivalence, imperfection and guilt. This open ended inquiry outlines a new way of knowing. The primary data are biographical. For the purpose of this critical reflective article I am a mother, and hence I refer to my gendered experience. The article attempts to explore how my social work practice is afforded a new interpretative lens and reconstruction after my own transition into motherhood.